Amino acid inspired microscale organization of metallic nanocrystals - Sailaja, G.; Nair, Balagopal; Gale, Julian; Yamaguchi, T. (R S C Publications, 2014)
Amino acid inspired micro-scale organization of platinum and silver nanocrystals and the complementary oligomerization of amino acids is reported. The spatial organization of the microstructures is highly species specific with unique morphologies corresponding to particular combinations of a metal–amino acid system. Alanine, glycine and glutamic acid were used to illustrate the concept. The presence of a poly(amino acid) or stabilizing agent alters the size and configuration of the microscale assembly. The molecular interaction between the Pt and the amino acid and the synthesis conditions play key roles in determining the final shape of these 3D structures. The method offers a very facile strategy for designing diverse molecular building blocks of metallic microstructures for advanced applications by choosing versatile combinations of metal-ions and amino acids. Platinum integrated structures, in addition to their diverse architecture, showed good stability at high temperatures. Electrochemical characterization of samples heat-treated at 400 °C showed a high platinum surface utilization of 41.5%.